Cross section measurements of deuteron induced nuclear reactions on natural tungsten up to 34 MeV. (March 2015) - Duchemin, C.; Guertin, A.; Haddad, F.; Michel, N.; Métivier, V.
Abstract: 186 g Re is a β -/ γ emitter of great interest for nuclear medicine. It has shown successful results on bone metastases palliation and has similar chemical properties as 99 m Tc, the most commonly used imaging agent. 186 g Re is routinely produced using rhenium target in nuclear reactor. Higher specific activity could be obtained using accelerators. In this paper, production cross section values are presented for the nat W( d, x ) 186 g Re reaction up to 34 MeV, using the stacked-foils method and gamma spectrometry. From this data set, the thick target production yield of 186 g Re is determined and compared with the validated values of the IAEA and also with the proton route. The production cross sections of the nat W( d, x ) 183, 182 g, 184 m, 184 g, 181 Re and nat W( d, x ) 187 W reactions have also been determined. A good agreement is found with the literature. Our data are compared with the version 1.6 (December 2013) of the TALYS code which shows discrepancies both on the shape and on the amplitude for these deuteron induced reactions. Abstract : Highlights: Deuteron induced reactions on natural tungsten up to 34 MeV. Experimental values were determined using the stacked-foil technique. Comparison with the TALYS code version 1.6. Thick target yield of 186 g Re, 183, 182 g, 184 m, 184 g, 181 Re and 187 W.